Loosening Evaluation of Bolted Joints Modified by Fine Particle Bombardment under Transverse Cyclic Loading. Issue 6 (2nd November 2018) - Zhang, Mingyuan; Zeng, Dongfang; Wang, Zhanqiang; Tang, Mingming; Lu, Liantao
ABSTRACT: The objective of this article is to evaluate the loosening behavior of bolted joints modified by fine particle bombardment (FPB) under transverse cyclic loading. FPB treatment was conducted to thread surfaces of both the bolt and the nut. Self-loosening experiments were then performed on the bolted joint with high, medium, and low preload using a fatigue testing machine. The test results show that fretting wear occurs at the thread surface under transverse cyclic loading, which leads to gradual self-loosening of bolted joints without the rotation of the nut. FPB treatment alleviates thread wear by increasing the surface hardness and reducing the friction coefficient between threads, thereby improving the anti-loosening ability of bolted joints. After FPB treatment, the bolted joints with a lower preload exhibited a greater relative improvement in anti-loosening ability than those at a higher preload.